2011
DOI: 10.1242/jcs.078436
|View full text |Cite
|
Sign up to set email alerts
|

Multivesicular bodies in the enigmatic amoeboflagellateBreviata anathemaand the evolution of ESCRT 0

Abstract: Endosomal sorting complexes required for transport (ESCRTs) are heteromeric protein complexes required for multivesicular body (MVB) morphogenesis. ESCRTs I, II, III and III-associated are ubiquitous in eukaryotes and presumably ancient in origin. ESCRT 0 recruits cargo to the MVB and appears to be opisthokont-specific, bringing into question aspects of the current model of ESCRT mechanism. One caveat to the restricted distribution of ESCRT 0 was the previous limited availability of amoebozoan genomes, the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…It has been proposed that TOM1 and Hrs could play parallel roles in clathrin recruitment and sorting of ubiquitylated cargoes on early endosomal membranes, for their subsequent delivery to the lysosomes. Recent phylogenetic analysis shows that TOM1 family proteins form an ancestral ESCRT-0 complex in the amoeboflagellate Breviate anathema (Herman et al, 2011), as well as in Dictyostelium discoideum (Blanc et al, 2009). The authors demonstrated that in Dictyostelium, DdTOM1 interacts with Esp15, a clathrin adaptor protein involved in EGFR internalization (Benmerah et al, 1998) and degradation by the ESCRT complex (Roxrud et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that TOM1 and Hrs could play parallel roles in clathrin recruitment and sorting of ubiquitylated cargoes on early endosomal membranes, for their subsequent delivery to the lysosomes. Recent phylogenetic analysis shows that TOM1 family proteins form an ancestral ESCRT-0 complex in the amoeboflagellate Breviate anathema (Herman et al, 2011), as well as in Dictyostelium discoideum (Blanc et al, 2009). The authors demonstrated that in Dictyostelium, DdTOM1 interacts with Esp15, a clathrin adaptor protein involved in EGFR internalization (Benmerah et al, 1998) and degradation by the ESCRT complex (Roxrud et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However D. discoideum contains instead a minimal, possibly ancestral ESCRT-0 in which DdTom1 interacts with ubiquitin, clathrin and the ESCRT-1 protein Tsg101 (Blanc et al, 2009). MVBs were also recently identified in the basal amoebozoan Breviata anathema, strengthening the conclusion that the ESCRTs' are a common feature of this supergroup (Herman et al, 2011). In mammals and plants several VpsE genes such as Vps37, Vps4, Vps32, Mvb12 and Bro1 have undergone gene duplications.…”
Section: Evolutionary Conservation Of Escrts'mentioning
confidence: 69%
“…Presently, our understanding of ESCRT in plants is relatively poor, and thus, working models based on studies of ESCRT in yeasts and mammals are often employed to infer the mechanisms of ESCRT assembly and function in plants. While this approach has generally proven to be valid because of the overall conserved nature of ESCRT function among evolutionarily diverse organisms, particularly during MVB biogenesis (35,61,62), there are also several features of ESCRT in plants that are distinct, including the ability of TOL proteins to compensate for the lack of ESCRT-0 proteins in terms of ubiquitinated cargo recognition and sorting (16,17). Thus, understanding how different tombusviruses appropriate the plant ESCRT machinery, apparently through different forms of molecular mimicry, as discussed below, not only gives important insight into how tombusviruses manipulate membranes to facilitate their replication but may also provide valuable clues to previously unexplored aspects of normal ESCRT assembly and function in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while the ESCRT machinery and its interaction network are relatively well conserved and have similar cellular functions in plants compared to yeasts and mammals (14,15), some key differences exist, which are not well understood. For example, homologs of mammalian and yeast ESCRT-0 do not exist in plants (16), and instead, recent work has identified the TOL family of proteins to be involved in early recognition of ubiquitinated cargo and their sorting to MVBs (17). However, the relationship between cargo recognition by TOL proteins and subsequent ESCRT recruitment and assembly has yet to be investigated.…”
mentioning
confidence: 99%